Reality and Filipino Scholarship - Sionil Jose, F. (Kasarinlan: Philippine Journal of Third World Studies; Vol 30 No 1 (2015): The 2015 TWSC Writeshop, 2016)
National Artist Jose’s keynote speech opens this issue. Mincing no words, he paints a critical picture of Philippine scholarship and its representation of realities in the country. For some, his assertions may trigger contrary arguments, for others an affirmation of long-held beliefs. He drew freely on his own vast experience as a journalist and writer, pointing to the traditions that shape Philippine life, and the importance of history and folklore in understanding the nation and its cultures. He ends with a profound conclusion, that knowledge is not wisdom, and that scholarship is not simply the search for truth, but also justice.
Keywords: Filipino Scholarship